FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KONDISI JARINGAN PERIODONTAL PADA IBU HAMIL DI WILAYAH KERJA UPTD PUSKESMAS I DENPASAR SELATAN TAHUN 2023 - I Nyoman Gejir; I Gede Surya Kencana; I Made Budi Artawa (Jurnal Kesehatan Gigi (Dental Health Journal), 2023)
The pregnant women is one group of the vulnerable in dental and oral diseases, because in generally there are behavior changes and hormonal changes. This situation can effect the condition of the women’s periodontal tissue. The objective of this study is to knows the influencing factors which correlation with the periodontal tissue in the pregnant women in work area of UPTD Puskesmas I Denpasar Selatan in 2023.This research is an analytic survey, has been done in April 2023, with the number of samples are 55 persons. The samples has been taken with accidental sampling. The data analyzed with Kruskal Wallis and Cramer’s V to know the correlation between dependent and independent variables.The results of this research shows that most of pregnant women have behavior brushing their teeth with very good criteria (47.3%). There is not the pregnant women with healthy periodontal tissue. There is significance correlation between the behavior of tooth brushing and the condition of periodontal tissue, that is the better behavior tooth brushing, the better condition of periodontal tissue, with the number of significance value of 0.016 (less than 0.05). There is strong correlation between the age of pregnancy and the condition of periodontal tissue, with the number of significancy value of 0.18 (more than 0.15).The conclusion of this research are most of pregnant women have behavior tooth brushing with very good criteria, and there are correlation among the behavior of tooth brushing, the age of pregnancy with the condition of periodontal tissue. Based on the conclusion of this research, it is recommended that after the pregnancy examination, the pregnant women are referred to the dental clinic, and enhance the dental health promotion effort through various media.